Potential of DMC and PODE as Fuel Additives for Industrial Diesel Engines - Nicholas O’Connell; Dominik Stümpfl; Rudolf Höß; Raphael Lechner (Fuels)
Dimethyl carbonate (DMC) and polyoxymethylene dimethyl ethers (PODE also known as OME) are possible diesel additives that can be produced sustainably using green methanol. DMC can be produced from CO2 and methanol, while PODE can be produced from methanol and formaldehyde. In this study both DMC and PODE were investigated as drop-in diesel fuel additives regarding material compatibility, injection behavior, as well as particle and exhaust emissions. Both DMC and PODE are known to be incompatible with certain materials used as seals in the fuel injection system. Therefore, the material compatibility of both neat DMC and PODE as well as blends with B0 was investigated, with both PFTE and FFKM showing good compatibility. The hydraulic injection behavior of DMC–diesel and PODE–diesel blends was investigated experimentally, showing the need for compensating injection quantities for DMC and PODE blends to match neat diesel power output due to their lower calorific values. Energetic compensation can be achieved by higher injection pressures or longer injection durations. Engine tests have been conducted with both DMC–diesel and PODE–diesel blends, demonstrating the potential to mitigate the particle–NOX trade-off.